Determinants of Perceived Good University Governance: The Roles of Internal Audit Existence, Functions, and Stakeholder Understanding - Najwa Khairina; Ahmad Afandi; Yudi Setiadi (aculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Indonesia higher-education institutions, including PTKIN, are expected to strengthen internal control and quality assurance as part of Good University Governance (GUG). Yet little research examines how students perceive internal audit in this governance framework. This study investigates whether students’ perceptions of the Internal Audit Unit’s visibility, roles, functions, and stakeholder understanding are associated with perceived GUG implementation in PTKIN. Based on survey data from 320 students in 22 PTKIN, complemented by interviews, observation, and document analysis, the study applies multiple linear regression with standard diagnostic tests. It contributes to the literature by emphasizing students’ perspectives on internal audit, which remain underexplored. Keywords: Internal Audit, Good University Governance, Islamic State Universities, Student Perceptions, Audit Role and Function